Cover Picture: Synthesis of Azahelicene N‐Oxide by Palladium‐Catalyzed Direct CH Annulation of a Pendant (Z)‐Bromovinyl Side Chain (Chem. Eur. J. 36/2013). Issue 36 (27th August 2013) - Kaneko, Eri; Matsumoto, Yuki; Kamikawa, Ken
<x xml:space="preserve">Abstract</x> Spiraling up the rings according to K. Kamikawa and co‐workers in their Communication on page 11837 ff.; they report that azahelicenes with a unique helical‐shaped backbone can be efficiently synthesized in high yields by utilizing palladium‐catalyzed CH annulation reactions. Functionalization at the C5 position in azahelicenes by using palladium‐catalyzed CH arylation also gave coupling products in good yields. These two CH bond activation processes can also be performed in one pot.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>